The Validity of Evidential Breath Alcohol Testing - Hodgson, Brian T. (Canadian Society of Forensic Science Journal, 2008)
The successful prosecution of drinking drivers under statutory limit laws ultimately must depend on scientifically sound results to prove the blood alcohol concentration of the offending driver. The great majority of these results are obtained by the measurement of alcohol in samples of breath from the driver. The scientific basis for evidential breath alcohol testing in well established. Experiments derived from a recognized scientific law in physics have proven the scientific validity of breath analysis to determine alcohol concentration in the blood. Instruments designed to measure breath alcohol content are based on technology that is capable of producing scientifically sound results. Like Canada, every country that embarks on evidential breath alcohol analysis subjects these instruments to a rigorous evaluation process. These processes determine whether the instruments meet the scientific standards for accuracy, precision, reliability and specificity. Moreover, to achieve scientifically sound results in operational use, user agencies must ensure that approved instruments are operated by qualified personnel using procedures based on good laboratory practice. This review covers the historical development of evidential breath alcohol analysis and its establishment as a legitimate means of measuring the concentration of alcohol in the blood of a suspected drinking-driver.
_eprint: https://doi.org/10.1080/00085030.2008.10757167